Association between six-minute walk distance and long-term outcomes in patients with pulmonary arterial hypertension: Data from the randomized SERAPHIN trial - Souza, Rogério; Channick, Richard N; Delcroix, Marion; Galiè, Nazzareno; Ghofrani, Hossein-Ardeschir; Jansa, Pavel; Le Brun, Franck-Olivier; Mehta, Sanjay; Perchenet, Loïc; Pulido, Tomás; Sastry, B K S; Sitbon, Olivier; et al. (PloS one, 2018)
BACKGROUND: Patients with pulmonary arterial hypertension who achieve a six-minute walk distance of 380-440 m may have improved prognosis. Using the randomized controlled trial of macitentan in pulmonary arterial hypertension (SERAPHIN), the association between six-minute walk distance and long-term outcomes was explored. METHODS: Patients with six-minute walk distance data at Month 6 were dichotomized as above or below the median six-minute walk distance (400 m) and assessed for future risk of pulmonary arterial hypertension-related death or hospitalization and all-cause death. Additionally, six-minute walk distance values at baseline, Month 6 and the change from baseline to Month 6 were categorized by quartiles. All associations were analyzed by the Kaplan-Meier method using a log-rank test and Cox regression models. RESULTS: Patients with a six-minute walk distance >400 m vs. ≤400 m at Month 6 have a reduced risk of pulmonary arterial hypertension-related death or hospitalization (hazard ratio 0.48; 95% confidence interval 0.33-0.69). The risk was also lower for patients with higher quartiles of six-minute walk distance at baseline or Month 6 (baseline: hazard ratio [Q4 (>430 m) vs. Q1 (≤300 m)] 0.23; 95% confidence interval 0.15-0.36; Month 6: hazard ratio [Q4 (>455 m) vs. Q1 (≤348 m)] 0.33; 95% confidence interval 0.19-0.55). In contrast, six-minute walk distance changes at Month 6 were not associated with the risk of pulmonary arterial hypertension-related death or hospitalization (p = 0.477). These findings were consistent when adjusted for known confounders. Similar results were observed for the risk of all-cause death up to end of study. CONCLUSIONS: Patients with pulmonary arterial hypertension walking >400 m had better long-term prognosis. Although changes in six-minute walk distance were not associated with long-term outcomes, assessing absolute six-minute walk distance values remains important in the clinical management of patients with pulmonary arterial hypertension.
Keywords: Walking; chůze; Female; Adult; dospělí; plicní hypertenze; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; Hypertension, Pulmonary; Prognosis; prognóza